SO2/NOx emissions and ash formation from algae biomass combustion: Process characteristics and mechanisms. (15th October 2016) - Zhao, Bingtao; Su, Yaxin; Liu, Dunyu; Zhang, Hang; Liu, Wang; Cui, Guomin
Abstract: The thermochemical conversion of algae biomass into energy via direct combustion is an important and effective way but emits pollutants. To address the gas pollutant emissions and ash characteristics in this process, three species of algae biomass, namely, Enteromorpha ( En ), Sargassum ( Sa ) and Chlorella ( Ch ), were used to investigate the process behavior of real-time SO2 /NOx emissions and ash formation at varied combustion temperatures. It was found that SO2 /NOx emission peaks and concentrations highly depended on the combustion temperature in addition to algae species. The SO2 emission amount and conversion ratio generally increased with increasing sulfur content in the algae. The NOx emissions were not causally related to the nitrogen content in the algae biomass. The conversion ratio from N to NOx for each algae species was similar at 700–900 °C. In particular, it was relatively low for the algae En and Ch, which have relatively high N contents, implying that a large amount of N exists in the form of reductive intermediates. Moreover, the morphological and physicochemical properties of the ash were also found to be associated with the combustion temperature and algae species. The results may provide a positive reference for pollution assessment and control from algae biomass combustion. Graphical abstract: Highlights: SO2 /NOx emissions and ash formation from direct combustion of three algae biomass. Emission characteristics of SO2 and NOx were addressed at varied temperature. S and N migration mechanisms were discussed. Morphological and physicochemical properties of algae ash were analyzed. The results may provide the control strategy for algae biomass combustion.